Strategi Bisnis Yang Tersirat Dalam Surat Al-Quraisy Ayat 1 – 4 - Muhamad Nurois Amin (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2020)
Abstract Broadly speaking, the interpretation of the Quraysh describes the enormous pleasure of Allah bestowed on the Quraysh tribe. However, if examined further, the interpretation of the Quroisy letter contains a business strategy in each of its sentences. There are eight business strategies contained in the Quroisy letter; first, perseverance, learning and habituation from childhood; second, Brand Equity and Master Brand which are described with lafaz quraish; third, outward expansion, building networks, as well as diplomacy and negotiation skills illustrated clearly. fourth, market segmentation which is described by lafaz al-shita’i wa al-saif; fifth, the balance between business and worship. Even business is used propaganda that is described by lafaz falya’budu; sixth, the positioning is described by lafaz al-bait. The seventh is resignation which is accompanied by hard work that is described by lafaz alladhi at'amahum min ju '; and eighth, dare to take risks described in lafaz wa a> manahum min khauf. Thus the Qur'an gives guidance to Muslims, especially those who run a business. The Koran not only provides guidance in matters of worship, but also in terms of mu'amalah. Keywords: bisnis, surat Al-Quraisy ayat 1 Abstrak Secara garis besar, penafsiran surat Quraisy menjelaskan kenikmatan Allah yang sangat besar yang dianugerahkan kepada suku Quraisy. Namun, jika dikaji lebih dalam lagi, penafsiran surat Quroisy ini mengandung strategi bisnis dalam setiap kalimat-kalimatnya. Terdapat delapan strategi bisnis yang terkandung dalam surat Quroisy; pertama, ketekunan, pembelajaran serta pembiasaan dari kecil, kedua, Brand Equity dan Master Brand yang digambarkan dengan lafaz quraish; ketiga, ekspansi ke luar, membangun network, serta keahlian diplomasi dan negosiasi yang digambarkan dengan lafaz rihlah; keempat, segmentasi pasar yang digambarkan dengan lafaz al-shita’i wa al-saif; kelima, balance antara bisnis dan ibadah. Bahkan bisnis digunakan dakwah yang digambarkan dengan lafaz falya’budu; keenam, positioning yang digambarkan dengan lafaz al-bait. Adapun yang ketujuh adalah tawakkal yang disertai dengan kerja keras yang digambarkan dengan lafaz alladhi at’amahum min ju’; dan kedelapan, berani mengambil risiko yang digambarkan dengan lafaz wa a>manahum min khauf. Demikianlah Alquran memberikan tuntunan kepada orang Muslim, khususnya bagi orang yang menjalankan suatu bisnis. Alquran tidak hanya memberikan tuntunan dalam hal ibadah, tetapi juga dalam hal mu’amalah.